Use of solar dryer and green coconut waste for energy production (Research, Society and Development, 2022)
The country's energy matrix has undergone changes, moving towards sustainability. To reduce the consumption of fossil fuels and the consequent emission of greenhouse gases, the use of briquettes presents itself as a viable and attractive alternative. The green coconut residue, which can be used for the manufacture of briquettes, is a biomass of natural, renewable origin and constitutes a large portion of urban waste. The following work has as main objective the energetic use of the green coconut husk in the form of briquettes. In one of the stages of manufacturing the briquettes, a solar dryer based on the IAPAR model produced with recycled material was used. Temperatures above 70°C were recorded inside the dryer, while the outside was around 30°C. Because of this, water is eliminated from the shells, which lose around 80% of their moisture in approximately 20 days. The literature points out that briquettes should be made with a moisture content of 8% to 23%, depending on the biomass. The briquettes were produced with a manual press and subjected to several analyzes based on NBR 8112/86, ASTM D5373/2008, ASTM D4208/2007 and NBR 8633/84. The analyzes showed the following results: fixed carbon content -1.71%, moisture - 16.58%, ash - 3.0%, volatiles - 95.30%, elemental chemical composition - Carbon 40.44%, Hydrogen 4 .26% and Sulfur 0.78%; upper calorific value - 15.36 MJ/kg and lower - 15.17 MJ/kg. According to the data obtained, it is possible to replace the firewood with coconut husk briquettes.